2015
DOI: 10.7763/ijcea.2015.v6.519
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Noble Metal (Ru, Os and Ag) on the Reduction Behaviour of Iron Oxide Using Carbon Monoxide: TPR and Kinetic Studies

Abstract: Abstract-This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
3
1
1
Order By: Relevance
“…According to these reports [19][20][21], the reduction of Fe 3 O 4 by carbon monoxide starts in the temperature range of ∼509-807°C, which was higher than the reduction temperature of Fe 3 O 4 in our study. e lower reaction temperature can be explained due to nanometer-sized Fe 3 O 4 , reacting with carbon monoxide more easily than crystalline Fe 3 O 4 .…”
Section: Characterization Of Fe 3 O 4 Nanoparticlescontrasting
confidence: 52%
See 1 more Smart Citation
“…According to these reports [19][20][21], the reduction of Fe 3 O 4 by carbon monoxide starts in the temperature range of ∼509-807°C, which was higher than the reduction temperature of Fe 3 O 4 in our study. e lower reaction temperature can be explained due to nanometer-sized Fe 3 O 4 , reacting with carbon monoxide more easily than crystalline Fe 3 O 4 .…”
Section: Characterization Of Fe 3 O 4 Nanoparticlescontrasting
confidence: 52%
“…e reduction temperature of the two-step reduction was approximately 285°C (Fe 3 O 4 ⟶ FeO) and 595°C (FeO ⟶ Fe). ese reduction reactions can be described as follows [19][20][21]:…”
Section: Characterization Of Fe 3 O 4 Nanoparticlesmentioning
confidence: 99%
“…Co and Fe catalysts were not reduced to metallic phases at a reduction temperature of 600 ℃. At a reduction temperature of 600 ℃, Co3O4 was reduced to CoO in the Co-Al catalyst, and Fe2O3 was reduced to Fe3O4 in the Fe-Al catalyst [32][33][34][35]. As a result, it was confirmed that the peaks of Ni, CoO, and Fe3O4…”
Section: Resultsmentioning
confidence: 93%
“…The last reduction peak at 400-600 • C indicates the reduction of magnetite to metallic Fe. Tengku et al [29] studied the effect of noble metals, such as Ru, on the reducibility of iron catalysts. They confirmed the promoting effect of ruthenium addition on the reducibility of iron oxides, which was established by shifting the reduction effects towards lower temperatures after introducing 3 wt% of ruthenium into the catalytic system.…”
Section: Resultsmentioning
confidence: 99%